Who likes to learn new things : measuring adult motivation to learn with PIAAC data from 21 countries - Gorges, Julia [Verfasser]; Maehler, Débora B. [Verfasser]; Koch, Tobias [Verfasser]; Offerhaus, Judith [Verfasser] (My University, 2016)
"Despite the importance of lifelong learning as a key to individual and societal prosperity, we know little about adult motivation to engage in learning across the lifespan. Building on educational psychological approaches, this article presents a measure of Motivation-to-Learn using four items from the background questionnaire of the Programme for the International Assessment of Adult Competencies (PIAAC)." (Author's abstract ; BIBB-Doku)
Keywords: G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; L 2 Lehr-Lerngestaltung; G 1.3.2 Bildungsverhalten und -verläufe; Lebenslanges Lernen; Lernmotivation; Weiterbildungsbereitschaft; PIAAC